Pharmacogenetics of Risperidone‐Induced Insulin Resistance in Children and Adolescents with Autism Spectrum Disorder. Issue 1 (30th March 2018) - Sukasem, Chonlaphat; Vanwong, Natchaya; Srisawasdi, Pornpen; Ngamsamut, Nattawat; Nuntamool, Nopphadol; Hongkaew, Yaowaluck; Puangpetch, Apichaya; Chamkrachangpada, Bhunnada; Limsila, Penkhae
Abstract: The purpose of this study was to explore the association of genetic polymorphism of genes related to pharmacokinetics or pharmacodynamics with insulin resistance in children and adolescents with autism spectrum disorder (ASD) and treated with risperidone. All 89 subjects underwent measurement of fasting blood glucose and insulin levels, body‐weight and height. Genotyping was performed by TaqMan real‐time polymerase chain reaction (PCR) (pharmacokinetics genes: cytochrome P450 2D6 ( CYP2D6 ) * 4 (rs3892097), *5 (gene deletion), *10 (rs1065852) and *41 (rs28371725), ATP‐binding cassette transporter B1 ( ABCB1) 2677 G>T/A (rs2032582) and 3435C>T (rs1045642) and pharmacodynamics genes: dopamine receptor D2 ( DRD2) Tag‐SNP (C>T) (rs4436578), DRD2 Tag1A (C>T) (rs1800497), leptin gene ( LEP) ‐2548G>A (rs7799039), ghrelin gene (GHRL) ‐604G>A (rs27647) and brain‐derived neurotrophic factor ( BDNF) 196G>A (rs6265)). Drug levels were analysed by liquid chromatography–tandem mass spectrometry (LC‐MS/MS). The results revealed that 5 (5.62%) patients presented with hyperglycaemia. Insulin resistance was detected in 15 (16.85%) patients. Insulin resistance was associated with LEP 2548 G>A and BDNF 196 G>A polymorphism ( p = 0.051 and p = 0.03). There was no association of pharmacokinetic gene polymorphisms ( CYP2D6 and ABCB1 ) and risperidone levels with insulin resistance. Multiple regression analysis indicated that BDNF 196 G>A polymorphism was significantly associated with insulin resistance ( p = 0.025). This finding suggested that BDNF 196 G>A polymorphism may be a genetic marker for predicting insulin resistance before initiating treatment in patients treated with risperidone. Because of the small sample size, further studies are needed to confirm these results.